The Problems of Compensation Employement Termination Due to Covid-19 - Betty Yunita Setyorini (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to answer employers dilemma during the Covid-19 pandemic to carry out labor efficiency by termination of work. The Cipta Kerja regulation number 11 of 2020 which is complemented by Government Regulation number 35 of 2021, as a normative basis for providing compensation for layoffs is considered a sufficiently mitigating solution when compared to previous labor legislation. However, what about the company's financial condition is not sufficient to provide compensation in accordance with the normative provisions of the legislation. To overcome this problem, an agreement is made between the employer and the workforce so that they can get a solution together. The agreement must also be registered with the Industrial Relations Court to protect the parties having an interest in it. Therefore, in writing this article, the Juridical Normative writing method is used, which analyzes cases based on applicable laws and regulations, analyzes legal concepts and qualitative descriptive methods.